Impact of sleep apnea treatment on cardiometabolic parameters in a large national multicenter alliance registry - Daniel Körfer; Wendy Cardenas; Lisa Davis; Shachi Patel; Mikhail N. Kosiborod; Melissa Magwire; Daniel Aistrope; Jonathan Fialkow; Adedapo IIuyomade; Harneet K. Walia (American Journal of Preventive Cardiology, 2025)
Purpose: To investigate the association of positive airway pressure (PAP) therapy and cardiometabolic factors in patients with sleep apnea (SA). Methods: Patients with cardiometabolic disease from a multicenter cardiometabolic registry from January 2019 to August 2023 were included. Baseline characteristics of patients with SA stratified by PAP use were compared. Logistic regression was used to assess the association of PAP use and cardiometabolic factors (Hemoglobin A1c [HbA1c], systolic and diastolic blood pressure [SBP and SDB], Triglycerides [TG] and body mass index [BMI]) in an unadjusted model (Model 1), after adjusting for age, sex, ethnicity, race, BMI (Model 2), and additionally for cardiac comorbidities, medications, and medication adherence (Model 3). Results: Of a total of 1575 patients (median age: 65 years [interquartile range 58.0–71.0], 683 (43.4 %) presented with SA, and of those, 447 (65.4 %) reported routine PAP use. Logistic regression analysis showed that PAP use was associated with lower HbA1c (-0.31 %, 95 % CI -0.59 to -0.04, p = 0.025) in Model 2, but not in Model 3 (-0.19 %, 95 % CI -0.46 to 0.08, p = 0.165). In addition, PAP use was associated with lower SBP (-3.99 mmHg, 95 % CI -7.18 to -0.8, p = 0.014) and lower DBP (-2.52 mmHg, 95 % CI -4.45 to -0.6, p = 0.010) in Model 3. Conclusions: In this multicenter registry of patients with cardiometabolic disease, PAP use was associated with improvement of cardiometabolic key risk factors. This effect was observed for SBP and DBP even after adjusting for medication adherence.